Analisis Gaya Kepemimpinan Dan Iklim Organisasi Terhadap Kinerja Karyawan (Studi pada Karyawan PT. Pos Indonesia (Persero) Cabang Boyolali) - Gunawan, Gunawan, Imron Rosyadi, S.E., M.Si (2017)
The research was based on the idea that every organization, good government/private goals will be achieved. Where the cooperation of the leaders and the led canperform the task or function - function within an existing organization sturktur surroundings. Human resources management requires open communication and relationships within the limits, the authority and responsibilities of each employee. So the influence of leadership styles And Organizational Climate Against the performance of an employee will give purpose and benefit for the benefit of the organization. This study aims to test and find out empirically (1) the influence of leadership styles on performance of employees (2) Organizational Climate influence on performance of employees (3) the influence of leadership styles and the climate of simultaneous Organisasisecara on performance of employees. The variables used in this study is the leadership style and Organizational Climate as the independent variable and the dependent variable as Employee Performance. The sample in this research are the employees of PT. Pos Indonesia (persero) Boyolalai branch as much as 43 respondents with sampling random sampling techniques. Method of data collection using the questionnaire. Data analysis techniques, namely multiple linear regression analysis, test, and test F t. t-test analysis results indicate there is a partial influence between independent variables the dependent variable whereas against test data F simultaneous influences showed a variable Climate and Organizational leadership style on performance of employees is seen through the results of the calculation Fhitungsebesar 76.344 > Ftabel of 3.23 with probability of 0.000 (pvalue < 0.05).